Thermoneutrality and severe malaria: investigating the effect of warmer environmental temperatures on the inflammatory response and disease progression - Vialard, Fiorella; Allaeys, Isabelle; Dong, George; Phan, Minh Phuong; Singh, Urvashi; Hébert, Marie Josée; Dieudé, Mélanie; Langlais, David; Boilard, Eric; Labbé, David P.; Olivier, Martin (Frontiers in Immunology, 2023)
Most studies using murine disease models are conducted at housing temperatures (20 – 22ºC) that are sub-optimal (ST) for mice, eliciting changes in metabolism and response to disease. Experiments performed at a thermoneutral temperature (TT; 28 – 31ºC) have revealed an altered immune response to pathogens and experimental treatments in murine disease model that have implications for their translation to clinical research. How such conditions affect the inflammatory response to infection with Plasmodium berghei ANKA (PbA) and disease progression is unknown. We hypothesized that changes in environmental temperature modulate immune cells and modify host response to malaria disease. To test this hypothesis, we conducted experiments to determine: (1) the inflammatory response of bone-marrow derived macrophages (BMDM) to infectious agents at different environmental temperatures and (2a) the inflammatory response to malarial agents injection in a peritonitis model and (2b) disease progression in PbA-infected mice at TT compared to ST. In one study, acclimatized mice were injected intraperitoneally with nHZ or Leishmania at TT (28 – 31ºC) or ST, and immune cells, cytokine, and extracellular vesicle (EV) profiles were determined from the peritoneal cavity (PEC) fluid. We found that Leishmania injection resulted in decreased cell recruitment and higher phagocytosis of nHZ in mice housed at TT. We found 398 upregulated and 293 downregulated pro-inflammatory genes in mice injected with nHZ, at both temperatures. We report the presence of host-derived EVs never reported before in a murine parasitic murine model at both temperatures. In another study, PbA-infected mice were monitored until end-point (i.e. experimental malaria score ≥4). We observed metabolic changes in mice housed at TT, but these did not result to noticeable changes in disease progression compared to ST. To our knowledge, these experiments are the first to investigate the effect of thermoneutrality on a malaria murine model. We found important metabolic difference in mice housed at TT. Our results offer insights on how thermoneutrality might impact a severe malaria murine model and directions for more targeted investigations.